Urban Manners : 15 Contemporary Artists from India. - von Früstenberg, Adelina; Hangar Bicocca, Milan (Geneva : ART for The World, 2007)
Chhachhi, Sheba ; Dodiya, Atul ; Dube, Anita ; Gupta, Probir ; Gupta, Subodh ; Kaleka, Ranbir ; Kallat, Jitish ; Kallat, Reena Saini ; Kher, Bharti ; Malani, Nalini et al.
Urban Manners : 15 Contemporary Artists from India, Hangar Bicocca, Milan, October 19, 2007 - January 6, 2008
kunstcatalogus